PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DI KANTOR KELURAHAN KADIDI KABUPATEN SIDENRENG RAPPANG - Jamal, Jusnita; Lukman; Andi Nilwana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Public service is one of the fundamental functions of government in meeting the needs of society and is an important indicator of the success of government administration. As a government unit that interacts directly with the community, the sub-district office plays a strategic role in providing public services. However, initial observations at the Kadidi Sub-District Office, Sidenreng Rappang Regency, indicated a gap between community expectations and the implementation of services in practice, including procedures perceived as complicated, service completion that was not always timely, and information regarding service requirements that had not been communicated optimally. These conditions may reduce community satisfaction, highlighting the need for an empirical study of the effect of service quality on community satisfaction. This study aims to examine the quality of public services, assess the level of community satisfaction, and determine the effect of service quality on community satisfaction at the Kadidi Sub-District Office, Panca Rijang District, Sidenreng Rappang Regency. This study is based on the concept of public service stipulated in Law Number 25 of 2009, Kotler’s (2016) theory of service quality consisting of five dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy, as well as the concept of community satisfaction measured through indicators of service procedures, service requirements, clarity of service officers, officer discipline, and service responsibility. This study employed a quantitative approach using a survey method. The population consisted of 3,435 residents of Kadidi Sub-District, with a sample of 97 respondents determined using the Slovin formula with a 90% confidence level and a 10% margin of error, employing simple random sampling. Data were collected through observation, questionnaires, and literature review, and were subsequently analyzed using descriptive statistics, validity and reliability tests, and simple linear regression analysis with the assistance of IBM SPSS Statistics. The results showed that the quality of public services at the Kadidi Sub-District Office was categorized as very good, with an achievement rate of 82.6%, while the level of community satisfaction was also categorized as very good, with an achievement rate of 81.6%. The reliability test indicated that both research instruments were valid and reliable, with Cronbach’s Alpha values of 0.922 and 0.861, respectively. The regression analysis produced the equation Y = 4.671 + 0.678X, with a correlation coefficient (R) of 0.883, indicating a very strong and positive relationship, and an R Square value of 0.779, meaning that service quality explained 77.9% of the variation in community satisfaction. The F-test result (334.884; sig. 0.000) and t-test result (18.300; sig. 0.000) demonstrated that service quality had a positive and significant effect on community satisfaction; therefore, H0 was rejected and H1 was accepted.